Management of Adult-Onset Still's Disease Patients in Intensive Care Unit: a Case Report - Andriani, Ika Jati Setya; Rakhmatjati, Pradana Bayu; Wisudarti, Calcarina Fitriani Retno; Widodo, Untung (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Adult-onset Still's disease (AOSD) is a rare inflammatory disorder characterized by the classic triad of fever, arthritis, and evanescent rash. AOSD is a multi-systemic disorder with unclear etiology. Glucocorticoids are the first line treatment for AOSD, and disease-modifying anti-rheumatic drugs (DMARDs) are often used in some patients with a poor response to glucocorticoids. Parenchymal lung involvement in AOSD is rare (only 5% of AOSD), one of them is acute respiratory distress syndrome (ARDS), where ARDS is the most severe complication. Management of such conditions in the intensive care unit (ICU) is crucial.Case: A 25-year-old woman came with unresolved fever for one week which was preceded by joint pain and reddish spots on the skin. The patient was diagnosed as AOSD complicated with ARDS due to pneumonia which kept the patient in the ICU for 24 days.Discussion: AOSD is a multigenic auto-inflammatory disorder involving the innate and adaptive immune systems. Based on Yamaguchi's criteria, the patient was diagnosed with AOSD where there was a high fever that lasted more than a week, arthritis, salmon rash, leucocytosis, sore throat, splenomegaly, alanine aminotransferase (ALT) abnormalities, and negative antinuclear antibodies (ANA) test. The first-line therapy given was methylprednisolone, doses were tapered gradually. As the patient didn't respond to therapy, she was then given immunosuppressive therapies such as cyclosporine, hydroxychloroquine and underwent therapeutic plasma exchange (TPE). The patients responded to treatments and showed good laboratory results.Conclusion: This case report describes a patient with AOSD that was diagnosed based on clinical manifestations and Yamaguchi criteria. The patient improved clinically with high dose administration of corticosteroids, immunosuppressive agents, and TPE. Making a correct diagnosis and starting an appropriate treatment as soon as feasible is crucial in this case as the patient suffers complications.